Characterisation of rust surfaces formed on mild steel exposed to marine atmospheres using XRD and SEM/Micro-Raman techniques. (September 2016) - de la Fuente, D.; Alcántara, J.; Chico, B.; Díaz, I.; Jiménez, J.A.; Morcillo, M.
Highlights: SEM/Micro-Raman is very useful for characterizing rust phases morphologies. SEM/Micro-Raman enables unequivocal rust phases identification. γ-FeOOH basically presents two types of morphologies: globular and laminar. Fe3 O4 presents two morphologies: flat patches and black doughnut-type formations. β-FeOOH presents highly porous morphologies comprised by fine prismatic crystals. Abstract: The exposure of mild steel to marine atmospheres gives rise to the formation of various corrosion products, mainly lepidocrocite, goethite, magnetite and akaganeite. In this study, Grazing Incidence X-Ray Diffraction, Micro-X-Ray Diffraction and Scanning Electron Microscopy/Micro-Raman are used to characterise rust layer surfaces and to identify the principal component rust phases and their morphology. The main conclusion reached is that lepidocrocite is preferentially located on the outermost surface while magnetite and akaganeite form mostly close to base steel. The Scanning Electron Microscopy/Micro-Raman technique has been very useful for characterising (identifying) the wide variety of morphologies presented by the rust phases.